A COMPARATIVE STUDY OF PSYCHOLOGICAL VARIABLES OF STATE AND NATIONAL LEVEL TENNIS PLAYERS - Singh, Surender; Singh, Karan; Singh, Vikram (International Journal of Research -GRANTHAALAYAH, 2024)
The present study aimed to understand the relationship between mindfulness, mental imagery, and subjective sports performance satisfaction. This study was done on male tennis players aged 18 to 28 years who play competitive tennis at the State and National Levels in India. The tools used to measure the variables were The Mindfulness Attention Awareness Scale (MAAS) by Brown & Ryan (2003), Sports Imagery Ability Questionnaire by Williams & Cumming (2014) and Athlete’s Subjective Performance Scale (ASPS) by Nahum et al. (2016). The results of the study show that the national-level tennis players had better self-reported satisfaction scores than the state-level players. Zero-order correlations showed that there was a statistically significant, moderate, positive correlation between Mindfulness and mental imagery (r(53) = -.304, n = 55, p < .05), indicating that subjective sports performance satisfaction had very little influence in controlling for the relationship between Mindfulness score and mental imagery.